2012
DOI: 10.5222/ankem.2012.086
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Lactic-Co-Glycolic Acid) Based Drug Delivery Devices For Tissue Engineering And Regenerative Medicine

Abstract: SUMMARYPoly (D,L-lactide-co-glycolide) ANKEM Derg 2012;26(2):86-98

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 78 publications
(104 reference statements)
1
15
0
1
Order By: Relevance
“…18,21 A previous report has suggested that PLGA is associated with an increased risk of arterial thrombosis in a rat model of carotid angioplasty, 17 however this result is to be interpreted cautiously given its small sample size (n=4). In addition, the high rate of thrombosis seen with the rapamycin-loaded PLGA-construct used might have been more strongly related to inherent cytotoxicity associated with the drug rather than to the biomaterial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,21 A previous report has suggested that PLGA is associated with an increased risk of arterial thrombosis in a rat model of carotid angioplasty, 17 however this result is to be interpreted cautiously given its small sample size (n=4). In addition, the high rate of thrombosis seen with the rapamycin-loaded PLGA-construct used might have been more strongly related to inherent cytotoxicity associated with the drug rather than to the biomaterial.…”
Section: Discussionmentioning
confidence: 99%
“…1417 Amongst the available biomaterials, PLGA is particularly appealing as it is biodegradable and FDA approved for use as a drug-delivery device. 18 Another option for local perivascular delivery in animal models is Pluronic F127 gel, which has established utility in early proof-of-concept studies. 19 Unfortunately, previous attempts at local delivery of anti-inflammatory agents to vasculature beds have been limited by significant toxicity associated with the drugs themselves, which delay rather than accelerate healing.…”
Section: Introductionmentioning
confidence: 99%
“…PLGA is a biodegradable synthetic polymer, which showed numerous advantages in tissue engineering applications [96]. The lack of bioactivity is the major drawback associated with PLGA [97]. The addition of bioactive glass can significantly improve the biological properties of PLGA-based scaffolds [98].…”
Section: Synthetic Polymer-based Biomaterialsmentioning
confidence: 99%
“…Among them, the most widely used polymer is poly( dl ‐lactide‐co‐glycolide) (PLGA). Many pharmaceutical substances have already been encapsulated in PLGA‐based delivery systems . The main advantage of PLGA particles as drug delivery systems is the ability to control the particle size, surface properties and rate of drug release from the polymer matrix, which allows to gain the site‐specific action of the drug at the optimal dosing regimen .…”
Section: Introductionmentioning
confidence: 99%